Oral appliances for the treatment of obstructive sleep apnea in patients with low C-PAP compliance: a long-term case series. Issue 4 (October 2014) - Marchese-Ragona, Rosario; Manfredini, Daniele; Mion, Marta; Vianello, Andrea; Staffieri, Alberto; Guarda-Nardini, Luca
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: To assess the effectiveness of mandibular advancement devices (MADs) for the treatment of obstructive sleep apnea syndrome (OSAS) over a long-term follow-up in patients non-compliant with continuous positive airway pressure (CPAP) and to identify potential predictive factors of response to MADs. Methods: Fifteen OSAS patients were enrolled. Apnea-hypopnea index (AHI) and daytime sleepiness were assessed at baseline and at the end of follow-up. Potential baseline predictors of treatment effectiveness were assessed. Results: AHI and Epworth Sleepiness Scale (ESS) scores improved significantly with MADs. Sixty per cent of patients were 'responders', of whom 33% were 'full responders'. Sixty-seven per cent of patients showed total compliance. No correlations between the potential predictors and the response to MAD therapy were found. Discussion: Effectiveness of MAD therapy was shown over a long-term follow-up in OSAS patients with low compliance to CPAP. Efforts to identify predictive success factors fell short.